Farmers' Behavior in Facing Risks in Ginger Farming - Wicaksono, Mochamad Setyo; Maswadi, Maswadi; Oktoriana, Shenny (Newinera Publisher, 2024)
Ginger is a medicinal plant with numerous uses across traditional industries, food sectors, and as an export commodity. Although ginger production in West Kalimantan reached 3,805.89 tons in 2022, this figure remains below the national average of 7,278.10 tons. Ginger farmers face various risks, including beetle pest attacks and rhizome rot diseases, leading to production fluctuations. This study aims to analyze the impact of farmers' behavior in facing production risks on the level of ginger production. The analysis was conducted using a production function regression with dummy variables representing farmers' behaviors, categorized into three groups: risk takers, risk neutral, and risk averters. The results indicate that farmers categorized as risk takers have 142.1% higher ginger production compared to risk averters, while risk-neutral farmers have 73.6% higher production. These findings demonstrate that farmers' behavior in managing production risks significantly influences ginger production levels.